Liability of Insurance Companies for Unfair Terms in Iranian Law - Reza Shahbazi; Samad Hazrati (Jurnal Cita Hukum, 2022)
Insurance has developed into a vast industry, so insurance companies seek to maximize profit. Therefore, they tend to formulate the insurance contracts in such a way that infringes on the insured's rights. They strive to secure additional privileges and profit by incorporating unfair terms in insurance contracts. Lawyers suggest that the solution to preventing the inclusion of such words and ensuring fair treatment of the insured lies in the insurers' pre-contractual duties, such as their obligation not to include such unfair terms. Based on the fairness principle in Iranian law, one can articulate this obligation for both parties in all contracts. In conclusion, in insurance contracts, the general contract terms obligate the insurer to accept payment from a third party. If paying the insurance premium takes place with the permission of the insured, the third party can return to the insured for the paid amount. However, if the third party performs the payment without the insured's permission (the primary debtor), it is gratis, and the third party retains the right to return to the insured.